Intracranial Hypertension and the use of External Ventricular Drain - EVD: Correct Management Avoids Complications (Global Journal of Medical Research, 2023)
Introduction Intracranial hypertension ICH is a neurological disorder caused by several factors The positioning of the external ventricular shunt EVD is considered the gold standard in the care of severe neurological patients being a surgical procedure with the purpose of draining the cerebrospinal fluid CSF to the outside It is a closed drainage system introduced into the skull to one of the cerebral ventricles in an operating room environment Correct handling prevents complications during the patient s recovery Objective To know the correct management with the external ventricular drain - EVD to avoid complications Methods This is a study with a qualitative bibliographic and descriptive approach The information was acquired through the LILACS BVS MEDLINE SCIELO database in Portuguese between the years 2003 and 2018 There are 09 articles and one book useful for research carefully read in the light of the objectives grouped and arranged in tables for better understanding of the results